PENGARUH PENAMBAHAN PEMLASTIS GLISEROL DAN MINYAK BUAH MERAH (Pandanus conoideus) TERHADAP KUAT TARIK DAN ELONGASI BIOPLASTIK BERBAHAN PATI SAGU (Metroxylon sago)-KITOSAN - Agnes Dyah Novitasari Lestari (FMIPA Universitas Papua, 2023)
The need for plastic will increase along with technological and industrial developments, thereby increasing the amount of plastic waste. Oil and gas based plastics are not biodegradable. One way to limit the amount of plastic waste is to use biodegradable plastics, also known as bioplastics. In this study, the bioplastic material used was sago starch from Papua combined with chitosan with the addition of glycerol plasticizers and red fruit (Pandanus conoideus) oil. The use of red fruit oil, apart from being a plasticizer, is also intended to provide antioxidant properties to the resulting bioplastics. The variation in the weight ratio of sago starch: chitosan used is 4:1 and 1:1. The volume of glycerol and red fruit oil added was equal, namely 2.5 mL. After bioplastics have been synthesized, tensile strength and elongation tests are carried out. The results showed that the tensile strength and elongation were greatly influenced by the type of plasticizer, both in sago starch:chitosan ratios of 1:1 and 1:4. The addition of red fruit oil significantly reduced the tensile strength, both in the sago starch:chitosan ratio of 1:1 and 1:4, but increased the elongation in the sago starch:chitosan ratio of 1:4. This indicates that red fruit oil can be used as a plasticiser candidate in bioplastics as antioxidant packaging.